Insect composition of Sungai Chukai mangrove forest in Terengganu, Malaysia based on selected sampling methods - Raja Alang, Raja Nurul Nadia (2015)
Insects are one of the most abundant organisms on earth and can be found almost everywhere in any types of ecosystem. However, their abundance in mangrove forest are hardly reported. In Malaysia, the study of insect in mangrove habitat is very crucial and most of the database were recorded in other regions. Therefore, the mangrove forest in Sungai Chukai, Kemaman, Terengganu was chosen as the study site and the area also has considered threatened due to the rapid development. This study was conducted to compare the abundance of insects in different zones, to determine the functional feeding group of insects, to compare the diversity of insects and lastly to investigate the relationship of abiotic factors with the abundance of insects in Sungai Chukai mangrove. The sampling activities were done in three times and four zones of the study area along Sungai Chukai were determined according to environmental factors and accessibility to the forest floor. A Malaise trap and three yellow pan traps were installed for three days and the samples were collected on the fourth day. As a result, 7772 of individuals insects comprising of 16 orders and 123 families were identified and the most abundance was recorded from the order of Diptera with 4072 of individuals (52.39%). While, the lowest individuals were recorded in three orders, namely; Dermaptera (0.01%),Microcoryphia (0.01%) and Neuroptera (0.01%), with one individual respectively. The number of individuals between the order of insects was significantly different (P<0.05) where the order of Diptera had shown the differences between the order of Dermaptera,Microcoryphia, Neuroptera, Mantodea, Odonata and Isoptera. The dominant of Diptera in Sungai Chukai was due to the type of traps applied which focused on flying insect and mangrove as the habitat preferences of flies itself. Furthermore, according to zonation, the insects were most abundant in Zone 3 (37.16%), and the lowest was recorded in Zone 2 (18.99%). The abundance of insect according to zonation also had showed sigificantly different between Zone 1 and Zone 3 (P<0.05). The differences occured due to the compact distribution of the vegetation and high diversity of flora provides sufficient food for the insects in Zone 3 compared with the othe zones. Besides, the diversity of insects along the riverine of Sungai Chukai mangrove was quite diverse with the H’ value was 3.41 and 0.71 for the evenness. For the similarity, Zone 1 was very dissimilar with the other zones due to the forest structure and also high level of disturbance which caused the difference of insect composition. However, the abiotic factors such as temperature, humidity and rainfall are not showing strong relationship with the abundance of insects. In conclusion, the composition of insect in Sungai Chukai are quite diverse since 16 orders from overall orders were recorded within the forest. Besides, due to forest disturbances, the diversity of insects was decreased during the study periods. Therefore, further action must be taken to conserve the insects and other flora and fauna before we lost the precious biodiversity in Sungai Chukai.